2009
DOI: 10.1590/s0103-90162009000100015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rust, early and late leaf spot resistance in wild and cultivated peanut germplasm

Abstract: Groundnut (Arachis hypogaea) has an AB genome and is one of the most important oil crops in the world. The main constraints of crop management in Brazil are fungal diseases. Several species of the genus Arachis are resistant to pests and diseases. The objective of our experiments was to identify wild species belonging to the taxonomic section Arachis with either A or B (or "non-A") genomes that are resistant to early leaf spot (Cercospora arachidicola), late leaf spot (Cercosporidium personatum) and rust (Pucc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 9 publications
4
44
0
6
Order By: Relevance
“…Data showed that accessions of A. ipaënsis and A. duranensis have higher concentrations of resveratrol than the two allotetraploids, which is a surprising result since many other studies showed differences between diploids and polyploids, the latter having better characteristics than the former (Fávero et al, 2009;Xu et al, 2014;Michelotto et al, 2015;Leal-Bertioli et al, 2015, 2017. The lack of polyploidy superiority has been previously observed for Arabidopsis thaliana and Pyrus communis, in which only a few metabolites differ between diploids and synthetic autotetraploids.…”
Section: Resveratrol Contentmentioning
confidence: 57%
See 2 more Smart Citations
“…Data showed that accessions of A. ipaënsis and A. duranensis have higher concentrations of resveratrol than the two allotetraploids, which is a surprising result since many other studies showed differences between diploids and polyploids, the latter having better characteristics than the former (Fávero et al, 2009;Xu et al, 2014;Michelotto et al, 2015;Leal-Bertioli et al, 2015, 2017. The lack of polyploidy superiority has been previously observed for Arabidopsis thaliana and Pyrus communis, in which only a few metabolites differ between diploids and synthetic autotetraploids.…”
Section: Resveratrol Contentmentioning
confidence: 57%
“…Sequences RSArAs01, RSArAs02, RSArAs06, RSArAhT05, RSArAhT06 were placed in different clusters as it can be seen in Figure 1. A. hypogaea and A. stenosperma sequences were chosen to primer design among the species that had amplicons sequenced since the first is the cultivated and previous data on RS expression is available (Chung et al, 2003;Zhu et al, 2014) and the second is a source of genes for A. hypogaea, since some of its accessions had more resistance to some diseases that affect the cultivated one (Fávero et al, 2009). Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-breeding research on crossings of A. hypogaea L. with wild germplasm has been conducted in Brazil with the aim of identifying sources of resistance to major pests and foliar diseases (Fávero, Simpson, Valls, & Vello, 2006;Fávero, Moraes, Garcia, Valls, & Vello, 2009;Janini, Boiça Júnior, Godoy, Michelotto, & Fávero, 2010;Michelotto et al, 2015;Santos et al, 2011;Santos, Godoy, Michelotto, & Fávero, 2013). One of the crosses made involved an elite cultivar from the Instituto Agronômico de Campinas (IAC 503) and the amphidiploid (A. magna x A. cardenasii) 4x .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated that A. kuhlmannii accessions V 8889 and V 7639 display resistance to fungal diseases including late and early leaf spot and rust (Fávero et al, 2009) and insects such as thrips and red-necked peanutworm (Michelotto et al, 2013). Therefore, understanding the complex set of plants currently grouped as A. kuhlmannii and related accessions would shed light on the taxonomy of this species, and provide potentially useful information for breeding programs.…”
Section: Introductionmentioning
confidence: 99%